Estimating cost savings of pharmacogenetic testing for depression in real-world clinical settings - Maciel A (Dove Medical Press, 2018)
Alejandra Maciel, Ali Cullors, Andrew A Lukowiak, Jorge Garces AltheaDx, San Diego, CA, USA Abstract: The burden of depression significantly impacts the patient, the health care system, and society, at large. Medication management guided by pharmacogenetics has been shown to increase therapeutic efficacy and improve symptoms in patients diagnosed with depression, but limited data are available on the cost savings of pharmacogenetic-guided interventions outside of psychiatric clinical specialties. Our study utilizes published health care costs and clinical patient outcome data to model the economic impact of pharmacogenetic-guided treatment for depression in a variety of clinical settings. Assuming a test cost of USD$2,000 for pharmacogenetic testing, the model predicts a savings of USD$3,962 annually per patient with pharmacogenetic-guided medication management. Keywords: pharmacogenetics, depression, personalized medicine, cost savings, pharmacoeconomics, psychotropic, cytochrome P450